FEATURES OF WINTERING WINTER RAPE AT DIFFERENT SEEDING RATES AND THE USE OF GROWTH REGULATORS - Бахмат, М. І.; Сендецький, І. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The studies results influence of the growth regulator Vermiyodis and sowing norms on wintering of winter oilseed rape plants and Mercedes hybrid on sod podzolic soils of the experimental field of Prykarpattia of the State Agricultural Experimental Station of the NASG region are presented. Studies have shown that the variants with the pre-sowing treatment off the winter variety Cheremosh seeds was carried out, on average over the years of research, at the sowing rate of 0600000 / ha plant death during overwintering was 4.7-5.7 pcs / m2 or 9, 5-10 , 8%, at a sowing rate of 0800000 / ha of germinating seeds - 5.7- 6.2 pieces / m2 or 8.5-9.3%, at a sowing rate of 1.0 million / ha of similar seeds - 8.7-9 , 3 pcs / m2 or 10.1- 10.9%. In the variants where the pre-sowing treatment of seeds was carried out with the Vermiyodis regulator at a dose of 5 l / t at a sowing rate of 08mln / ha, the plant death was 4.6-5.6%, which is 2.8-3.0% less than the norm sowing 1.0 million / ha of germinating seeds. In the variants where the pre-sowing treatment of seeds of the winter hybrid Mercedes was carried out with the growth regulator "Vermiodis" 5 l / t, the percentage of dead plants was 4.8-5.6% at the sowing rate of 0600000 / ha of germinating seeds, at the sowing rate of 0.8 million / ha - 6.1-7.3%, with a sowing rate of 1.0 million / ha of germinating seeds 8.1-8.6%, which is significantly less than the control and options, where presowing seed treatment was carried out with the growth regulator "Vermijodis". Studies have shown that the best overwintering, on average over the years of research, was in the rapeseed variety of winter hybrid Mercedes at a sowing rate of 0600000 / ha of germinating seeds, in the variety Cheremosh at a sowing rate of 0800000 / ha of germinating seeds for pre-sowing seed treatment.